Prosthesis–Patient Mismatch after Aortic Valve Replacement with the Mosaic Ultra Bioprosthesis - Ntinopoulos, Vasileios; Biefer, Hector Rodriguez Cetina; Dushaj, Stak; Rings, Laura; Fleckenstein, Philine; Dzemali, Omer; Haeussler, Achim (The Thoracic and Cardiovascular Surgeon, 2023)
Background Several studies have reported high rates of prosthesis–patient mismatch (PPM) after aortic valve replacement (AVR) with the Mosaic prosthesis. This work assesses the incidence of PPM after AVR with a modified version of the Mosaic prosthesis, the Mosaic Ultra.Methods We performed a retrospective analysis of the data of 532 patients who underwent AVR with implantation of the Mosaic Ultra prosthesis in the period 2007–2016 in our institution. Patients were classified according to their indexed effective orifice area (EOAi) to severe (EOAi < 0.65 cm2/m2), moderate (EOAi 0.65–0.85 cm2/m2), and absent/mild PPM (EOAi > 0.85 cm2/m2). In-hospital postoperative outcomes and the impact of PPM on mean transvalvular pressure gradient after stratification by prosthesis size were assessed.Results Overall, 3 (0.6%) patients had severe, 92 (17.3%) moderate, and 437 (82.1%) absent/mild PPM. There was a significant difference in PPM proportions (moderate/severe vs absent/mild PPM) across different prosthesis sizes overall (p < 0.0001), observing gradually increasing rates of PPM with decreasing prosthesis sizes. Patients with moderate/severe PPM had higher mean transvalvular pressure gradients (19 [13–25] vs 13 [10–17] mm Hg, p < 0.0001) than patients with absent/mild PPM. There was a significant difference in mean transvalvular pressure gradient between the different aortic valve prosthesis sizes overall (p < 0.0001), observing gradually increasing gradients with decreasing prosthesis sizes.Conclusion Patients undergoing AVR with the smaller sized (19, 21, and 23 mm) Mosaic Ultra aortic valve prostheses exhibit a higher risk for moderate/severe PPM and higher mean aortic transvalvular pressure gradients than patients receiving the larger sized (25, 27, and 29 mm) prostheses.
Keywords: aortic valve and root; heart valve surgery; outcomes